THE NATIONAL ECONOMY THE SALT BLEND BEING FORMED ON EVAPORATOR SYSTEM OF THE BELARUSIAN STEEL WORKS - A. A. Ledneva; A. I. Rozhkov (Литьë и металлургия)
Application of the sand-salt mixture with the salt rest for winter maintenance of roads, formed on evaporator system of the Belarusian metallurgical works is considered.